2021
DOI: 10.3390/pharmaceutics13081285
|View full text |Cite
|
Sign up to set email alerts
|

Thermodynamic Stability Is a Strong Predictor for the Delivery of DARPins to the Cytosol via Anthrax Toxin

Abstract: Anthrax toxin has evolved to translocate its toxic cargo proteins to the cytosol of cells carrying its cognate receptor. Cargo molecules need to unfold to penetrate the narrow pore formed by its membrane-spanning subunit, protective antigen (PA). Various alternative cargo molecules have previously been tested, with some showing only limited translocation efficiency, and it may be assumed that these were too stable to be unfolded before passing through the anthrax pore. In this study, we systematically and quan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 35 publications
2
7
0
Order By: Relevance
“…We find that the efficiency of ZF5.3-mediated protein delivery to the cytosol is highest when the protein cargo readily unfolds under physiological conditions. Similar findings that low thermodynamic stability enhances intracellular delivery have been reported for toxin-mediated delivery of DARPins and even cytosolic penetration of antisense oligonucleotides, suggesting that the relationship between folding and endosomal escape may apply broadly to the passage of therapeutic macromolecules across cellular membranes.…”
Section: Discussionsupporting
confidence: 71%
“…We find that the efficiency of ZF5.3-mediated protein delivery to the cytosol is highest when the protein cargo readily unfolds under physiological conditions. Similar findings that low thermodynamic stability enhances intracellular delivery have been reported for toxin-mediated delivery of DARPins and even cytosolic penetration of antisense oligonucleotides, suggesting that the relationship between folding and endosomal escape may apply broadly to the passage of therapeutic macromolecules across cellular membranes.…”
Section: Discussionsupporting
confidence: 71%
“…Previously, we showed that the delivery of various DARPin cargoes to the cytosol of Flp-In 293-EpCAM-BirA cells is dependent on thermodynamic stability, probably due to the required unfolding step when traversing the pore. We carried out these experiments using an assay employing cells stably overexpressing the epithelial cell adhesion molecule (EpCAM) as the receptor to be targeted, and E. coli biotin ligase (BirA), stably expressed in the cytosol, to biotinylate the avi tag attached to the cargo once it has reached the cytosol 25 . We thus confirmed the presence of cytosolic DARPin cargoes, and thereby the successful translocation, by utilizing the BirA assay previously developed 24 .…”
Section: Resultsmentioning
confidence: 99%
“…Unfolding of the cargo is required for delivery through anthrax pores. The ability to translocate to the cytosol was compared for DARPins with different thermodynamic stabilities and as a conclusion, delivery through anthrax pores was suggested to be probably limited to molecules that unfold easily [ 141 ]. High stability was not limiting for delivery of Pseudomonas exotoxin A-based cargoes in the study by Verdurmen et al from 2015 [ 118 ], although unfolding is also required for the route of Pseudomonas exotoxin A.…”
Section: Toxins For Therapymentioning
confidence: 99%
“…Although feasible in principle, the approach is limited to a selection of molecules that have to fulfil multiple criteria that are essential for an effect after passing toxin routes, for example, certain properties of cargo molecules as discussed previously [ 141 ]. This considerably narrows down the choice of cargo molecules.…”
Section: Toxins For Therapymentioning
confidence: 99%